IMPLEMENTASI LAYANAN BIMBINGAN DAN KONSELING TERHADAP PEMULIHAN PSIKOSOSIAL ANAK KORBAN PENYALAHGUNAAN NARKOBA DI LEMBAGA REHABILITAS NARKOBA MUSI RAWAS - Herwantoro; Fadila; Syamsul Rizal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of guidance and counseling services toward psychosocial recovery of children affected by drug abuse at Musi Rawas Drug Rehabilitation Institution. The study employed a qualitative approach with a case study design. Research informants included counselors, rehabilitation managers, rehabilitated children, and family members. Data were collected through observation, in-depth interviews, and documentation. Data analysis used Miles and Huberman’s interactive model consisting of data reduction, data display, and conclusion drawing. The results indicate that counseling services were implemented through individual counseling, group counseling, social guidance, spiritual development, and family assistance. These services positively contributed to psychosocial recovery, including improved self-control, better social relationships, increased self-confidence, and behavioral changes toward positive adaptation